Організаційно-управлінська система хокею в Україні - Павлюк, І.; Pavliuk, I. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Розглянуто систему організації та керування хокеєм в Україні та надано ретроспективний аналіз літературних даних із проблем модифікації сучасного спорту, тенденцій розвитку хокею на сучасному етапі, його комерціалізації та професіоналізації. Опитування проводилося серед керівників федерації хокею України, керівників і спортсменів українських хокейних клубів, а також серед спортсменів, членів національної збірної команди України (в опитуванні брав участь 21 респондент). Оцінено систему організації та управління хокеєм в Україні, визначено особливості його виникнення і становлення, проблеми та перспективи його розвитку в Україні, організаційно-правові, соціально-політичні й економічні умови функціонування. . System of the organization and management of ice hockey in Ukraine. The system of the organization and management of hockey in Ukraine has been researched. Besides, the retrospective analysis of the literary data on a problem of updating of modern sports, tendencies of development of hockey at the present stage, its commercialization and professionalism have been presented. The interview has been conducted among the leaders of Ukraine ice hockey federation, leaders and sportsmen of the Ukrainian hockey clubs, and also among sportsmen, members of national team of Ukraine (21 people took part in the interview). The system of organization and management of hockey in Ukraine has been evaluated. The peculiarities of its origin and development have been defined. The problems and prospects of development, as well as organizational, legal, socio-political and economic conditions of its functioning have been revealed.
The System of the Organization and Management of Ice Hockey in Ukraine.
Keywords: хокей; управління; комерціалізація; професіоналізація; функціонування; Hockey; management; commercialization; professionalization; functioning; 796.03